Plant epigenetics: phenotypic and functional diversity beyond the DNA sequence. Issue 4 (22nd April 2021) - Boquete, M. Teresa; Muyle, Aline; Alonso, Conchita
Abstract : Phenotypic variation determines the capacity of plants to adapt to changing environments and to colonize new habitats. Deciphering the mechanisms contributing to plant phenotypic variation and their effects on plant ecological interactions and evolutionary dynamics is thus central to all biological disciplines. In the past few decades, research on plant epigenetics is showing that (1) epigenetic variation is related to phenotypic variation and that some epigenetic marks drive major phenotypic changes in plants; (2) plant epigenomes are highly diverse, dynamic, and can respond rapidly to a variety of biotic and abiotic stimuli; (3) epigenetic variation can respond to selection and therefore play a role in adaptive evolution. Yet, current information in terms of species, geographic ranges, and ecological contexts analyzed so far is too limited to allow for generalizations about the relevance of epigenetic regulation in phenotypic innovation and plant adaptation across taxa. In this report, we contextualize the potential role of the epigenome in plant adaptation to the environment and describe the latest research in this field presented during the symposium "Plant epigenetics: phenotypic and functional diversity beyond the DNA sequence" held within the Botany 2020 conference framework in summer 2020.